Potential regulatory role of gibberellic and humic acids in sprouting of Chlorophytum borivilianum tubers - Nakasha, Jaafar Juju; Sinniah, Uma Rani; Puteh, Adam; Hassan, Siti Aishah (Hindawi Publishing Corporation, 2014)
Tubers of safed musli (Chlorophytum borivilianum) were immersed in three different concentrations of gibberellic acid (GA3) or humic acid (HA) prior to planting. The highest concentration of GA3 (20 mg  ) and all concentrations of HA (5, 10, and 15%) appeared to hasten tuber sprouting and promote uniform sprouting pattern. The use of 20 mg  GA3 or 15% HA successfully improved sprouting and mean sprouting time. Safed musli growth and development was improved through the increase in the number of leaves, total leaf area, leaf area index, and total fibrous root length. This directly influenced the number of new tubers formed. The use of 20 mg  GA3 or 15% HA gave similar response with nonsignificant difference among them. However, due to the cost of production, the result from this study suggests that 15% HA should be used to obtain improved sprouting percentage, homogeneous stand establishment, efficient plant growth and development, and increased yield of safed musli.